Networking essentials : a CompTIA Network+ N10-007 textbook - Beasley, Jeffrey S., 1955-; Nilkaew, Piyasat (Pearson, 2018)
Thoroughly updated to reflect the CompTIA Network+ N10-007 exam, Networking Essentials, Fifth Edition is a practical, up-to-date, and hands-on guide to the basics of networking. Written from the viewpoint of a working network administrator, it requires absolutely no experience with either network concepts or day-to-day network management. Networking Essentials, Fifth Edition guides readers from an entry-level knowledge in computer networks to advanced concepts in Ethernet and TCP/IP networks; routing protocols and router configuration; local, campus, and wide area network configuration; network security; wireless networking; optical networks; Voice over IP; the network server; and Linux networking. This edition contains additional coverage of switch security, troubleshooting IP networks, authorization and access control, best practices for disaster recovery, network infrastructure configuration and management, data traffic network analysis, network security, and VoIP. It also covers approximately 250 new terms now addressed by CompTIA's N10-007 exam. Clear goals are outlined for each chapter, and every concept is introduced in easy-to-understand language that explains how and why networking technologies are used. Each chapter is packed with real-world examples and practical exercises that reinforce all concepts and guide you through using them to configure, analyze, and fix networks. KEY PEDAGOGICAL FEATURES NET-CHALLENGE SIMULATION SOFTWARE provides hands-on experience with entering router and switch commands, setting up functions, and configuring interfaces and protocols WIRESHARK NETWORK PROTOCOL ANALYZER presents techniques and examples of data traffic analysis throughout PROVEN TOOLS FOR MORE EFFECTIVE LEARNING AND NETWORK+ PREP, including chapter outlines, summaries, and Network+ objectives WORKING EXAMPLES IN EVERY CHAPTER to reinforce key concepts and promote mastery KEY TERM DEFINITIONS, LISTINGS, AND EXTENSIVE GLOSSARY to help you master the language of networking QUESTIONS, PROBLEMS, AND CRITICAL THINKING QUESTIONS to help you deepen your understanding.